1995
DOI: 10.1038/bjc.1995.348
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitisation of spontaneous multidrug resistance by a 1,4-dihydropyridine analogue and verapamil in human glioma cell lines overexpressing MRP or MDR1

Abstract: Summary Multidrug resistance phenotypes in human tumours are associated with the overexpression of the 170 kDa P-glycoprotein encoded by the multidrug resistance 1 (MDRI) gene, and also with that of the non-P-glycoprotein-mediated multidrug resistance gene, MRP, which encodes a 190 kDa membrane ATPbinding protein. We Cancer, 58, 860-864, 1994). In this study, we investigated whether chemosensitising agents of P-glycoprotein-mediated multidrug resistance such as verapamil, a biscoclaurine alkaloid (cepharan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…Digoxin is not a substrate for Bcrp [58], but other studies have indicated that the poor BBB permeability of digoxin is not explained by P-gp alone [11,38]. Verapamil has been used as a P-gp inhibitor in concentrations from 5 to 150 μM [23,[59][60][61], but it has also been shown to inhibit Mrp activity in concentrations of 5-10 μM [45,62] as well as Bcrp activity, although not in the concentration range applied here [63,64]. In our study, 50 μM verapamil lowered the efflux ratio of digoxin to 1.1, whereas the Bcrp inhibitor, Ko 143, had no effect on the digoxin transport indicating that the verapamil inhibition of A-L digoxin transport we observed was due to inhibition of P-gp or Mrp's.…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 99%
“…Digoxin is not a substrate for Bcrp [58], but other studies have indicated that the poor BBB permeability of digoxin is not explained by P-gp alone [11,38]. Verapamil has been used as a P-gp inhibitor in concentrations from 5 to 150 μM [23,[59][60][61], but it has also been shown to inhibit Mrp activity in concentrations of 5-10 μM [45,62] as well as Bcrp activity, although not in the concentration range applied here [63,64]. In our study, 50 μM verapamil lowered the efflux ratio of digoxin to 1.1, whereas the Bcrp inhibitor, Ko 143, had no effect on the digoxin transport indicating that the verapamil inhibition of A-L digoxin transport we observed was due to inhibition of P-gp or Mrp's.…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 99%
“…24) To determine the expression of the individual MRP1, MRP2, MRP3, we established specific probes for each MRP family member by polymerase chain reaction (PCR) amplification. Levels of mRNA were quantified densitometrically with a Fujix BAS 2000 bio imaging analyzer (Fuji Photo Film Co., Tokyo).…”
Section: )mentioning
confidence: 99%
“…Moreover, DOX shows reduced efficacy against tumor cell populations that exhibit the 'classical' P-gp MDR phenotype, as well as those with an altered topoisomerase II activity. Thus, numerous efforts were made to both generate structural analogues that improve the antitumor potency of DOX while lowering its toxicity and to circumvent cellular drug resistance mechanisms [11][12][13]. Recently, P-gp expression and in vitro uptake of DOX were studied in glioblastoma and endothelial cell lines [14].…”
Section: Introductionmentioning
confidence: 99%